2018
DOI: 10.1038/s41567-017-0018-3
|View full text |Cite
|
Sign up to set email alerts
|

Destabilizing turbulence in pipe flow

Abstract: Turbulence is the major cause of friction losses in transport processes and it is responsible for a drastic drag increase in flows over bounding surfaces. While much effort is invested into developing ways to control and reduce turbulence intensities [1][2][3] , so far no methods exist to altogether eliminate turbulence if velocities are sufficiently large. We demonstrate for pipe flow that appropriate distortions to the velocity profile lead to a complete collapse of turbulence and subsequently friction losse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
121
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 91 publications
(145 citation statements)
references
References 30 publications
(42 reference statements)
18
121
0
1
Order By: Relevance
“…Furthermore, such perturbations may provide insights for control applications in order to eliminate turbulence. In agreement with the recent experimental observations of Kühnen et al [23], we find that highly-turbulent initial conditions with flat axial velocity profiles could lead to a complete laminarization. Via edge-tracking, we show that these initial conditions are indeed on the laminarizing side of the edge state's stable manifold.…”
supporting
confidence: 93%
See 4 more Smart Citations
“…Furthermore, such perturbations may provide insights for control applications in order to eliminate turbulence. In agreement with the recent experimental observations of Kühnen et al [23], we find that highly-turbulent initial conditions with flat axial velocity profiles could lead to a complete laminarization. Via edge-tracking, we show that these initial conditions are indeed on the laminarizing side of the edge state's stable manifold.…”
supporting
confidence: 93%
“…Furthermore, ref. [23] measured transient growth due to the non-normality of the linearized Navier-Stokes operator assuming the mean profile to be the base flow. They found that the transient growth was substantially suppressed when the profile was flattened.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations